New Trends in Agri-Food Sector: Environmental, Economic and Social Perspectives - Testa, Riccardo; Migliore, Giuseppina; Schifani, Giorgio; Tóth, József (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The agri-food sector has faced several challenges in recent years. The increase in the global population, and thus, growing food demand has led to the over-exploitation of numerous agricultural systems by farmers and agri-food entrepreneurs. However, in most cases, producers prioritize increasing their incomes, neglecting to consider the environmental and social impacts of their production processes. The search for ever greater yields and revenues has degraded agro-ecosystems, forcing both farmers and agri-food firms leave rural areas. Moreover, as global warming requires us to rethink existing production processes from economic, environmental and social points of view to reduce GHGs emissions, it is necessary to adopt sustainable agri-food production. This reprint contains empirical studies and systematic reviews regarding the achievement of a sustainable agri-food sector by assessing entrepreneurs' choices, consumer behavior and policy interventions.